Women and business : roles to combine - Rojas Valdez, Kelly (2020)
The paper presents the contribution of women in the business field. Within this field, there has been some progress, but organizations still need to continue working. Studies show that there are objective differences between men and women, capacities that both can develop, as well as characteristics that stand out more in women than in men in a particular approach. According to the review of the literature about women and the company, the findings indicate characteristics that most predispose in women are her communication skills, the integration of her thoughts, the management of her personal emotions, the empathy with people and with the company, the promotion of organized teams, the promotion of a better work environment, and the conduct of an effective management. The slow progress to improve in the professional career is also highlighted in this research, for this reason is necessary the importance of having conciliation practices in companies so that the woman can be maintained in the employment or move up in her professional career, it is also essential to have these for those companies that wish to maintain or cultivate the human talent, promote equal opportunities, demonstrate responsible social behavior, promote human rights, as well as exhibit their impacts, practicing business ethics that intent to serve as an example.